MHC class II genes mediate susceptibility and resistance to coronavirus infections in bats - Schmid, Dominik W; Meyer, Magdalena; Wilhelm, Kerstin; Tilley, Tatiana; Link-Hessing, Thomas; Fleischer, Ramona; Badu, Ebenezer K; Nkrumah, Evans Ewald; Oppong, Samuel Kingsley; Schwensow, Nina; Tschapka, Marco; Baldwin, Heather J; et al. (Molecular ecology, 2023)
Understanding the immunogenetic basis of coronavirus (CoV) susceptibility in major pathogen reservoirs, such as bats, is central to inferring their zoonotic potential. Members of the cryptic Hipposideros bat species complex differ in CoV susceptibility, but the underlying mechanisms remain unclear. The genes of the major histocompatibility complex (MHC) are the best understood genetic basis of pathogen resistance, and differences in MHC diversity are one possible reason for asymmetrical infection patterns among closely related species. Here, we aimed to link asymmetries in observed CoV (CoV-229E, CoV-2B and CoV-2Bbasal) susceptibility to immunogenetic differences amongst four Hipposideros bat species. From the 2072 bats assigned to their respective species using the mtDNA cytochrome b gene, members of the most numerous and ubiquitous species, Hipposideros caffer D, were most infected with CoV-229E and SARS-related CoV-2B. Using a subset of 569 bats, we determined that much of the existent allelic and functional (i.e. supertype) MHC DRB class II diversity originated from common ancestry. One MHC supertype shared amongst all species, ST12, was consistently linked to susceptibility with CoV-229E, which is closely related to the common cold agent HCoV-229E, and infected bats and those carrying ST12 had a lower body condition. The same MHC supertype was connected to resistance to CoV-2B, and bats with ST12 were less likely be co-infected with CoV-229E and CoV-2B. Our work suggests a role of immunogenetics in determining CoV susceptibility in bats. We advocate for the preservation of functional genetic and species diversity in reservoirs as a means of mitigating the risk of disease spillover.
Keywords: Animals; Coronavirus Infections; coronavirus; CoV-229E; Histocompatibility Antigens Class II; Chiroptera; Genes, MHC Class II; cryptic diversity; pathogen resistance; Coronavirus; koronavirové infekce; Hipposideros bat species complex; lidský koronavirus 229E; Phylogeny; major histocompatibility complex; geny MHC třídy II; zvířata; fylogeneze; MHC antigeny II. třídy; Coronavirus 229E, Human